Diversidade genética de palma forrageira (Opuntia spp.) acessada por marcador ISSR - Alencar, Girlene Maria de (2021)
The forage cactus (Opuntia spp.), which has Mexico as its center of origin, is the focus of this study, which aims to characterize the diversity of this important genetic resource that is essential for the sustainability of the Brazilian semiarid region, in order to provide the Active Germplasm Bank for the improvement of these accessions, aiming at achieving the best agronomic characteristics in relation to resistance to cochineal carmine (Dactylopius opuntiae). By analyzing the genetic diversity of 25 accessions of the species: Opuntia atropes Rose, O. cochenillifera (L.) Salm Dyck subgenus Nopalea, O. robusta var. larreyi (FAC Weber) Bravo, O. robusta Wendl., O. stricta Haw, O. undulata Griffiths and O. joconostle through molecular characters, using primers ISSR - 807, ISSR - 808, ISSR - 809, ISSR - 810 , ISSR - 811, ISSR - 818, ISSR - 825, ISSR - 827, ISSR - 834, ISSR - 840, ISSR - 841, ISSR - 842 AND ISSR - 868 with an annealing temperature of 50°, which amplified 1091 bands, of which 125 were polymorphic and 14 monomorphic. The obtained fragments were converted into a binary matrix and from this matrix it was possible to establish the genetic dissimilarity between individuals. This molecular technique proved to be efficient to estimate that among species, the 37 x 14 and 37 x 76 accessions of the species O. cochenilifera and O. atropes, respectively, are the most indicated as potential parents, as they have dissimilarity equal to 1 and has the same ploidy level, 2n=2x=22; and within the species, the accessions 13 x 14, 75 x 76 and 76 x 85 of the species O. atropes, and of the species O. cochenillifera, the accessions 37 x 42, with a divergence index of 1, are the most indicated as potential parents for the breeding program of Opuntia spp. Regarding accession 82 (O. joconostle), the molecular analysis corroborates the phenotypic and cytological analysis that this access actually belongs to the species O. stricta, due to its similarity with accessions in this group, mainly accession 75. The Coefficient of Cophenetic Correlation (CCC) for the Tocher cluster was 0.884** while the Cophenetic Correlation Coefficient obtained in the cluster analysis was 0.95***, showing greater consistency in the hierarchical cluster using Ward's criteria.